1988
DOI: 10.1021/ma00184a022
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the crystal lattice modulus and the Young's modulus of polyethylene

Abstract: 1653(26) Broze, G.; Jerome, R.; Teyssie, Ph.; Marco, C. J. Polym. Sci., (27) Broze, G.; Jerome, R.; Teyssie, Ph.ABSTRACT: T h e temperature dependence of the crystal lattice modulus of polyethylene was measured by X-ray diffraction with use of ultradrawn films produced by gelation/crystallization from dilute solution. Measurements were carried out in the temperature range 20-150 "C for specimens with draw ratios >300. T h e measured crystal lattice modulus was in the range 211-222 GPa, and the values were inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…118 GPa on the basis of the theoretical analysis described elsewhere. 19 This indicates no temperature dependence of crystal lattice modulus of PET along the chain direction, as has been reported for PE 23 PP, 24 and PVA. 10 In contrast, the other crystal moduli decrease with increasing temperature.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…118 GPa on the basis of the theoretical analysis described elsewhere. 19 This indicates no temperature dependence of crystal lattice modulus of PET along the chain direction, as has been reported for PE 23 PP, 24 and PVA. 10 In contrast, the other crystal moduli decrease with increasing temperature.…”
supporting
confidence: 67%
“…This procedure was represented elsewhere in detail. 15,16,23 For simultaneous biaxially stretched films, this model corresponds to a series model at ¼ 1, while it corresponds to a parallel model at ¼ 1. In following discussion, some final equations are described to shorten this paper.…”
Section: Resultsmentioning
confidence: 99%
“…8). In this connection it is worth recalling the thorough examination of elastic properties of ultra drawn polyethylene films reported by Matsuo and Sawatari [122,123]. Investigation of X-ray diffraction from the stretched films showed that elastic moduli of polyethylene crystals are practically independent of temperature up to 145°C while Young's modulus of the films decreased with temperature.…”
Section: Temperature Dependence Of Young's Modulusmentioning
confidence: 84%
“…But this may not happen in fact. A very recent study indicates that the crystal modulus of polyethylene is independent of temperature (32). However, the modulus of imperfect polyethylene fibers ( K = 21 1 to 222 GPA a t 20°C) decreases with increasing temperature apparently a s a result of decreasing crystallinity as T increases (32).…”
Section: Discussionmentioning
confidence: 98%